Nuclear import of the glucocorticoid receptor-hsp90 complex through the nuclear pore complex is mediated by its interaction with Nup62 and importin β - Echeverría, P.C. (2009)
Glucocorticoid receptor (GR) is cytoplasmic in the absence of ligand and localizes to the nucleus after steroid binding. Previous evidence demonstrated that the hsp90-based heterocomplex bound to GR is required for the efficient retrotransport of the receptor to the nuclear compartment. We examined the putative association of GR and its associated chaperone heterocomplex with structures of the nuclear pore. We found that importin β and the integral nuclear pore glycoprotein Nup62 interact with hsp90, hsp70, p23, and the TPR domain proteins FKBP52 and PP5. Nup62 and GR were able to interact in a more efficient manner when chaperoned by the hsp90-based heterocomplex. Interestingly, the binding of hsp70 and p23 to Nup62 does not require the presence of hsp90, whereas the association of FKBP52 and PP5 is hsp90 dependent, as indicated by the results of experiments where the hsp90 function was disrupted with radicicol. The ability of both FKBP52 and PP5 to interact with Nup62 was abrogated in cells overexpressing the TPR peptide. Importantly, GR cross-linked to the hsp90 heterocomplex was able to translocate to the nucleus in digitonin-permeabilized cells treated with steroid, suggesting that GR could pass through the pore in its untransformed state. Copyright © 2009, American Society for Microbiology. All Rights Reserved.